2006
DOI: 10.1029/2005ja011554
|View full text |Cite
|
Sign up to set email alerts
|

Magnus force in the Venus ionosphere

Abstract: [1] The retrograde superrotation motion of the Venus ionosphere is included in a study of the configuration of the ionospheric transterminator flow by using a fluid-dynamic interpretation of the interaction that takes place between both flow motions. It is argued that the interaction leads to a fluid dynamic force (Magnus force) that produces an overall ($10°) dawnward directed deflection of the transterminator flow which is comparable to that implied from the PVO observations. The Magnus force results from a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 17 publications
1
10
0
Order By: Relevance
“…In addition, asymmetric pickup of exospheric ions by magnetosheath electric and magnetic fields was shown to affect ionopause height [ Phillips et al , 1988]. Another physical process that could influence asymmetries in hole occurrence and ionopause height is the Magnus force [ Pérez‐de‐Tejada , 2006].…”
Section: Hole Characteristics and Locationmentioning
confidence: 99%
“…In addition, asymmetric pickup of exospheric ions by magnetosheath electric and magnetic fields was shown to affect ionopause height [ Phillips et al , 1988]. Another physical process that could influence asymmetries in hole occurrence and ionopause height is the Magnus force [ Pérez‐de‐Tejada , 2006].…”
Section: Hole Characteristics and Locationmentioning
confidence: 99%
“…The solar wind approaching Venus is slowed down by the mass loading with ions from the extended exosphere [Nagy et al, 1981] and shielded out by the highly conductive ionosphere [Luhmann et al, 2004]. Between the bow shock and ionopause, plasma transitions observed on both Venus [Shefer et al, 1979;Romanov et al, 1979;Phillips and McComas, 1991] and Mars [Lundin et al, 1990a[Lundin et al, , 1990b suggest that the solar wind transports momentum to the planetary particles [Pérez-de Tejada et al, 1995, the wave-particle interaction has been suggested to play an important role in this process by Pérez-de Tejada et al [2009]. As a result of solar wind slowing down around the planet, the IMF frozen in the solar wind piles up and stretches along the solar wind flow in the flanks of the planet.…”
Section: Introductionmentioning
confidence: 99%
“…Substituting our dimensionless quantities (70) and variables (71) into the differential equation (68) yields:…”
Section: The Exact Structure Of a Single Vortexmentioning
confidence: 99%
“…The form (83) is a convenient form for numerical calculations of the vortex energy. By using our dimensionless quantities (70) and variables (71), the energy (83) can be made dimensionless yielding:…”
Section: The Exact Structure Of a Single Vortexmentioning
confidence: 99%
See 1 more Smart Citation